A greyhound, a groundhog - Jenkins, Emily, 1967-; Appelhans, Chris (New York : Schwartz & Wade, 2017)
A tongue twister featuring a little round greyhound and a little round groundhog who work themselves into a frenzy as they whirl around and around one another.
Keywords: Stories in rhyme; Greyhounds -- Fiction; Dogs -- Fiction; Woodchuck -- Fiction; Tongue twisters; JUVENILE FICTION / Concepts / Words; JUVENILE FICTION / Concepts / Size & Shape; JUVENILE FICTION / Animals / Dogs